PENATAAN INSTALASI LISTRIK RUMAH TAHFIDZ QURAN AN-NUR CIREBON JAWA BARAT - Irawati, Irawati; Sunardi, Ariyawan; Gunawan, Wawan; Kartikasari, Deasy; Gazali, Ria (SWADIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The community service was held at the An-Nur Quran memorization house in Cirebon, West Java. The target is to help the An-Nur Quran memorization house whose electrical installations are still not organized. If left unchecked, this can result in the children of the tahfiz quran house being easily exposed to electric shock, and there can be a short circuit of electricity, making it easy for a fire to occur. Based on the location survey and our observations in the field, the lighting installation in the local area is still not suitable for use. The current phenomenon of electrical installations is still not well considered by the community, so there are many fire disasters everywhere caused by short circuits. Due to the lack of knowledge of the community and the installer about electrical science and electrical installation requirements. Therefore, electrical installations need to be properly arranged following PUIL guidelines so that accidents caused by electricity can be avoided. The PKM implementation mechanism includes the stages of (1) Formation of an independent service team consisting of lecturers and students; (2) Site survey, consultation, and negotiation with the local government; (3) Deliberation in determining work patterns and programs; and (4) Preparation of tools and materials for service activities. The PKM activity resulted in the repair and arrangement of electrical installations at the An-Nur Quran memorization house in Cirebon, West Java, including lighting installations on the terrace of the Quran memorization house according to PUIL guidelines.Pengabdian Kepada Masyarakat yang diselenggarakan bertempat di rumah tahfidz quran An-Nur Cirebon Jawa Barat. Adapun sasarannya adalah untuk membantu Rumah tahfiz Quran An-Nur yang instalasi listriknya masih belum tertata rapi. Jika dibiarkan, hal ini dapat mengakibatkan anak-anak rumah tahfiz quran akan mudah terkena sengatan listrik, dan lebih dikhawatirkan lagi dapat terjadi hubung singkat aliran listrik, sehingga mudah terjadi kebakaran. Berdasarkan survei lokasi serta pengamatan kami di lapangan, instalasi lampu pada daerah setempat masih belum layak untuk digunakan. Fenomena saat ini instalasi listrik masih menjadi hal yang sepeleh bagi masyarakat, sehingga banyak terjadi bencana kebakaran dimana – mana yang disebabkan oleh hubungan singkat arus listrik. Hal ini di karenakan kurangnya pengetahuan masyarakat maupun pihak instalator mengenai ilmu kelistrikan dan persyaratan instalasi kelistrikan. Oleh karena itu, instalasi listrik perlu ditata dengan benar sesuai dengan pedoman PUIL agar peristiwa kecelakaan akibat listrik dapat dihindari. Mekanisme pelaksanaan PKM meliputi tahapan (1) Pembentukan tim pengabdian mandiri yang terdiri dari dosen dan mahasiswa; (2) Survei lokasi, konsultasi dan negoisasi dengan pemerintah setempat; (3) Musyawarah dalam menentukan pola dan program kerja; dan (4) Penyiapan alat dan bahan untuk kegiatan Pengabdian. Kegiatan PKM menghasilkan perbaikan dan penataan instalasi listrik di Rumah tahfiz quran An-Nur Cirebon Jawa Barat termasuk pemasangan instalasi penerangan teras rumah tahfiz quran sesuai pedoman PUIL